Effects of plyometric exercise and motivation on the explosive power of volleyball players' limb muscles - Bayu Anggoro; Masrun Masrun (Jorpres (Jurnal Olahraga Prestasi), 2023)
This study aims to explore the effect of plyometric training forms, namely Depth Jump and Jump to Box, as well as training motivation on the explosive ability of volleyball players of Club Putra Kubang Jaya. Using a quasi-experimental method with a treatment design by Level 2 x 2, the population in this study was 20 people who were still actively training volleyball players from the Putra Kubang Jaya Club. The sample is 20 people with the sampling technique is total sampling. Training motivation data was measured using questionnaires, while volleyball players' explosive power ability was measured through vertical jump tests. Data analysis was performed using two-path ANOVA at significance level α=0.05 and Shapiro-Wilk Sig. normality test 0.05, followed by the Tukey test. The results of the data analysis showed that: 1) Sig. 0.00 0.05 were obtained, There are differences in the effect of plyometric depth jump training forms and jump to box plyometric training forms on the explosive power of leg muscles of volleyball players of Putra Kubang Jaya Club Pekan Baru City. 2) The results of Sig. 0.000.05 were obtained, There was an interaction between the form of plyometric depth jump training, the form of plyometric jump to box training, and the motivation to train on the explosive ability of the leg muscles of volleyball players of the Kubang Jaya Men's Club in Pekan Baru City. 3) Sig. 0.000.05 was obtained, In the high motivation group, the plyometric depth jump training form was more effective than the jump-to-box plyometric exercise form of volleyball players of the Putra Kubang Jaya Club, Pekan Baru City. 4) Sig. 0.0120.05 was obtained, in the low training motivation group, the plyometric jump-to box exercise form was more effective than the plyometric depth jump exercise form to increase the explosive ability of the leg muscles of volleyball players of the Putra Kubang Jaya Club, Pekan Baru City. Thus, this study concluded that the plyometric form of the Depth Jump exercise was more effective for increasing the explosive power ability of leg muscles in the high-motivation group, while the Jump to Box was more effective for the low-motivation training group